The Relationship Between Women's Birth Beliefs and Their Depression, Anxiety, Stress, and Pregnancy Avoidance - Barut, Sümeyye; Güney, Esra; Uçar, Tuba (Ordu Üniversitesi, 2022)
Objective: This study was conducted to determine the relationship between women's birth beliefs and their depression, anxiety, stress, and pregnancy avoidance.Methods: This web-based study was conducted in Turkey between September 2021 and October 2021. The study was completed with 619 participants. Personal Information Form, Birth Beliefs Scale (BBS), Depression Anxiety Stress Scale-Short Form (DASS), and Desire to Avoid Pregnancy (DAP) were used to collect the data.Results: The mean scores of women in the Natural and Medical Process Birth Belief (NPBS/MPBS) were determined as NPBS 4.31±0.68, MPBS 3.65±0.69 respectively. It was determined that there was a weak positive relationship between MPBS and DASS-Depression/Anxiety/Stress, and that this relationship was statistically significant (r=0.107, r=0.081, r=0.100, respectively; p<0.05). That the mean MPBS scores of the women who had a low level of education and a high income and were unemployed, and the women using modern family planning methods were statistically higher (p<0.05).Conclusion: In the study, it was determined that there was a positive relationship between depression, anxiety and stress levels of women who considered birth as a medical process, and that women's medical beliefs about birth affected their education and income levels, employment status and the use of modern family planning.
Keywords: Health Care Administration; Sağlık Kurumları Yönetimi